Stress tests and capital requirement disclosures: Do they impact banks' lending and risk-taking decisions? - Paul Konietschke; Steven Ongena; Aurea Ponte Marques (European Central Bank (ECB), 2022)
How do banks respond to changes in capital requirements as a result of the stress tests? Does the disclosure of stress test results matter? To answer these questions, we study the impact of European stress tests on banks' lending, their corresponding risk-taking, the ensuing effect on their profitability and the respective publication effect. Exploiting the centralised European stress tests in conjunction with two unique confidential databases containing (i) stress test information for the 2016 and 2018 exercises covering a total of 93 and 87 banks, respectively; and (ii) quarterly supervisory information on approximately 1000 banks (stress-tested and non-tested), allow us to implement a dynamic differencein- differences strategy for a comparable sample of banks. We find that banks participating in the stress tests reallocate credit away from riskier borrowers and towards safer ones in the household sector, making them in general safer but also less profitable. This is especially the case for the set of banks part of the Supervisory Review and Evaluation Process with undisclosed stress tests, which were also not disclosing their Pillar 2 Requirements voluntarily. Our results confirm that the publication of capital requirements can have a disciplinary effect since banks publishing their requirements tend to have more robust capital ratios, which improves market discipline and financial stability.
Keywords: E51; E58; G21; G28; 330; Stress-testing; Credit supply; Profitability; Financial stability; Market discipline